Nickel hypersensitivity following closure of atrial septal defect: A case report and review of the literature. (29th January 2018) - Dickison, Philippa; Harris, Victoria; Smith, Saxon D
Abstract: We present an unusual case where symptoms of headache and chest pain persisted for 3 years following the implantation of a septal occluder device for an atrial septal defect despite endothelialisation of the device. The patient was found to have nickel hypersensitivity on patch testing. Following the removal of the device the patient had complete resolution of headaches and chest pain up to 10 months post‐explantation.